2022
DOI: 10.6018/cpd.494741
|View full text |Cite
|
Sign up to set email alerts
|

Funcionamiento cognitivo y rendimiento deportivo en jóvenes futbolistas: una revisión sistemática

Abstract: Cognitive functioning is acquiring special relevance when studying the factors that influence soccer performance. Although the relationship between cognitive functions and sport performance has an extensive literature in adult soccer players, the same does not happen in young players, where this association has not been explored in depth. This work arises with the objective of knowing the state of the issue and going in depth in this line of research in youth categories, between 8 and 19 years old. For this pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Under mental fatigue, the available research has shown impaired technical actions(Badin et al, 2016) and tactical behaviours(Coutinho et al, 2015), which is likely to result from a lower ability to identify and use the relevant cues from the environment(Boksem et al, 2006), as well as from a slower and worst decision-making process. From this perspective, measuring and understanding the cognitive load imposed by different tasks on the players is of paramount importance to allow coaches to adjust the cognitive load during the week.Cognitive load refers to the mental effort required to complete a task(Peñalosa et al, 2022). From a neurocognitive perspective, understanding cognitive load is critical because it can affect our ability to learn, solve problems, and perform tasks efficiently(Romine et al, 2020;Zghibi et al, 2021).…”
mentioning
confidence: 99%
“…Under mental fatigue, the available research has shown impaired technical actions(Badin et al, 2016) and tactical behaviours(Coutinho et al, 2015), which is likely to result from a lower ability to identify and use the relevant cues from the environment(Boksem et al, 2006), as well as from a slower and worst decision-making process. From this perspective, measuring and understanding the cognitive load imposed by different tasks on the players is of paramount importance to allow coaches to adjust the cognitive load during the week.Cognitive load refers to the mental effort required to complete a task(Peñalosa et al, 2022). From a neurocognitive perspective, understanding cognitive load is critical because it can affect our ability to learn, solve problems, and perform tasks efficiently(Romine et al, 2020;Zghibi et al, 2021).…”
mentioning
confidence: 99%